Four behavioral tests associated with fear and aggressiveness in Japanese quail - Caliva, Jorge Martín (2022)
Male and Female adult japanese quail (Coturnix coturnix) were evaluated in 4 tests, performed aproximately 30 days appart from each other. Partial mechanical restraint test , Social Interaction, Tonic Inmovility and Welfare assesment